2022
DOI: 10.1088/1674-1056/ac447f
|View full text |Cite
|
Sign up to set email alerts
|

Pump pulse characteristics of quasi-continuous-wave diode-side-pumped Nd:YAG laser

Abstract: The influence of pumping laser pulse on the property of quasi-continuous-wave diode-side-pumped Nd:YAG laser is investigated theoretically and experimentally here. Under remaining a fixed duty cycle, the average output power increases, and the corresponding thermal focal length shorten with the increase of the pump pulse duration, which attributes to the decrease of the ratio of pulse buildup time to the pulse duration. At a pump power of 146 W, the laser output power changes from 65.1 W to 81.2 W when the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…And the experimentally measured thermal focal length value is greater than 3 m. Combined with the measured thermal focal length value and theoretical analyses of laser cavity mode, it can be concluded that the marked ranges a and b correspond to the power-stable region and mode-stable region within LEDpumped CW solid-state laser's optimal working stability zone, while the marked mode-stable region c and power-stable region d within the traditional LD-pumped CW solid-state laser are optima work stability zone. [19][20][21][22][23][24][25]25] Due to the thermal accumulation from LED CW pumping, the temperature difference between the crystal's interior and thermal distortion gradually increase, resulting in a transition from range a to range b in the laser stable area. Moreover, the value of thermal focal length gradually becomes smaller, and the value of the fundamental mode spot radius ω 0 and mode volume also decreases accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…And the experimentally measured thermal focal length value is greater than 3 m. Combined with the measured thermal focal length value and theoretical analyses of laser cavity mode, it can be concluded that the marked ranges a and b correspond to the power-stable region and mode-stable region within LEDpumped CW solid-state laser's optimal working stability zone, while the marked mode-stable region c and power-stable region d within the traditional LD-pumped CW solid-state laser are optima work stability zone. [19][20][21][22][23][24][25]25] Due to the thermal accumulation from LED CW pumping, the temperature difference between the crystal's interior and thermal distortion gradually increase, resulting in a transition from range a to range b in the laser stable area. Moreover, the value of thermal focal length gradually becomes smaller, and the value of the fundamental mode spot radius ω 0 and mode volume also decreases accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we analyze the emission mechanism of LEDs and address the coupling efficiency of LED-pumped lasers using non-diffuse scattering LEDs to rationalize the five-way pumping structure of LEDs. [16][17][18] To further enhance the intracavity photon number density, we adopt a high-efficiency LED-pumped two-rod Nd,Ce:YAG lasercavity structure. Under 80 W pump energy, a maximum average power of 11 W at 1319 nm is achieved at a repetition rate of 100 Hz in quasi-continuous wave (QCW) operation.…”
mentioning
confidence: 99%